Effect of Synthesis Medium on the Structure and Physicochemical Properties of Biomineral Composites Based on Hydroxyapatite and Hyaluronic Acid - Kalmykova, T. P.; Kostina, Yu. V.; Ilyin, S. O.; Bogdanova, Yu. G.; Severin, A. V.; Ivanov, P. L.; Antonov, S. V. (Polymer science. Series B, 2020)
Dispersions based on sodium hyaluronate and hydroxyapatite, which is synthesized both by the classical method in an aqueous medium to obtain submicron particles and in a bioactive hyaluronan medium with the formation of nanosized particles, are obtained. The synthesized hydroxyapatite nanoparticles have a complex structure based on a monodentate complex hyaluronan–Ca 2+ which remains in the dispersion both when adding a hyaluronan solution and when diluted with water. Physicochemical methods show that there is a significant difference between the energy characteristics of the surfaces of biocomposites obtained from dispersions. The rheology of dispersions of hydroxyapatite micro- and nanoparticles is investigated, the effect of dispersed phase concentration on it is revealed, and the viscoplastic behavior of dispersions of microparticles is demonstrated. This behavior disappears upon addition of the hyaluronan solution, which, however, leads to the loss of stability by the system. The introduction of hydroxyapatite nanoparticle additives into hyaluronan solutions has a weak effect on the rheology; no flocculation of nanoparticles occurs. The resulting composites consisting of hydroxyapatite and sodium hyaluronate can be considered a basis of a drug for the rehabilitation treatment of periodontitis.